2020
DOI: 10.1186/s12934-020-01316-1
|View full text |Cite
|
Sign up to set email alerts
|

Yeast display platform technology to prepare oral vaccine against lethal H7N9 virus challenge in mice

Abstract: Background: Existing methods for preparing influenza vaccines pose the greatest challenge against highly pandemic avian influenza H7N9 outbreak in the poultry and humans. Exploring a new strategy for manufacturing and delivering a safe and effective H7N9 vaccine is needed urgently. Results: An alternative approach is to develop an influenza H7N9 oral vaccine based on yeast display technology in a timely manner. Hemagglutinin (HA) of A/Anhui/1/2013 (AH-H7N9) is used as a model antigen and characterized its expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Saccharomyces cerevisiae is an ideal eukaryotic host and has been engineered to express bacterial, viral or tumour antigens [ 24 ]. Oral vaccination of S. cerevisiae surface-displayed vaccine candidates has shown promise for preventing bacterial or viral infection [ 25 27 ]. In our previous studies, oral administration of H7N9 HA on the surface of S. cerevisiae provided 100% protective efficacy against homologous virus challenge in a mouse model [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharomyces cerevisiae is an ideal eukaryotic host and has been engineered to express bacterial, viral or tumour antigens [ 24 ]. Oral vaccination of S. cerevisiae surface-displayed vaccine candidates has shown promise for preventing bacterial or viral infection [ 25 27 ]. In our previous studies, oral administration of H7N9 HA on the surface of S. cerevisiae provided 100% protective efficacy against homologous virus challenge in a mouse model [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral vaccination of S. cerevisiae surface-displayed vaccine candidates has shown promise for preventing bacterial or viral infection [ 25 27 ]. In our previous studies, oral administration of H7N9 HA on the surface of S. cerevisiae provided 100% protective efficacy against homologous virus challenge in a mouse model [ 25 ]. Furthermore, the immunogenicity of UreB or VacA of Helicobacter pylori ( H. pylori ) expressed on the S. cerevisiae surface was also investigated [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional injection administration of EBY100/pYD1-HA in mice provided effective immune protection against A (H5N1) virus challenge [15]. Furthermore, we generated another yeast-based H7N9 oral vaccine could also protect mice from A (H7N9) challenge [20]. In the present study, we extend our previous work by investigating the immunogenicity of EBY100/pYD1-HA with oral administration and evaluating the cross-protective immunity of EBY100/pYD1-HA in chicken model.…”
Section: Discussionmentioning
confidence: 61%
“…Quanti cation of HA protein was determined by indirect enzyme-link immunosorbent assay (ELISA) as described previously [20]. In a brief, 5 OD 600nm of EBY100/pYD1-HA pellets were re-suspended in 100 µL…”
Section: Ethics Statementmentioning
confidence: 99%
“…We have previously shown that EBY100/pYD1-HA could provide protection when administered by injection route in a mouse model 15 . However, EBY100/pYD1-HA induces serious inflammation at the injection site due to the diameter of S. cerevisiae is approximately 10 μm 19 , 20 . Furthermore, chickens are the primary model for studies of pathogenicity and vaccine efficacy studies for poultry 21 .…”
Section: Introductionmentioning
confidence: 99%